2011
DOI: 10.1039/c0cp02549f
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up approaches in production of aqueous nanocolloids of low solubility drug paclitaxel

Abstract: Nano-encapsulation of poorly soluble anticancer drug was developed with sonication assisted layer-by-layer polyelectrolyte coating (SLbL). We changed the strategy of LbL-encapsulation from making microcapsules with many layers in the walls for encasing highly soluble materials to using very thin polycation / polyanion coating on low soluble nanoparticles to provide their good colloidal stability. SLbL encapsulation of paclitaxel resulted in stable 100-200 nm diameter colloids with high electrical surface ξ-pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 18 publications
4
54
0
Order By: Relevance
“…In the top-down method, the particle size of drugs is reduced by high-pressure homogenization or milling 3739. On the other hand, in the bottom-up method, particle size is controlled by the probe sonication method; furthermore, particle size growth is inhibited by using antisolvents 40,41. The preparation method of top-down method is as follows: first, presuspension was prepared by a homogenizer and then the presuspension was processed using a high-pressure homogenizer or microfluidizer.…”
Section: Introductionmentioning
confidence: 99%
“…In the top-down method, the particle size of drugs is reduced by high-pressure homogenization or milling 3739. On the other hand, in the bottom-up method, particle size is controlled by the probe sonication method; furthermore, particle size growth is inhibited by using antisolvents 40,41. The preparation method of top-down method is as follows: first, presuspension was prepared by a homogenizer and then the presuspension was processed using a high-pressure homogenizer or microfluidizer.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies demonstrate that using NPs for delivery of drugs [95, 96] and/or herbs [14] can (a) better reach their intended targets in the cells of the body; and (b) reduce the total amount of an agent needed to accomplish a therapeutic effect [74]. NP herb or drug forms can not only bypass or dramatically improve upon the poor gastrointestinal absorption and/or solubility problems that limit the usefulness of many different bulk form agents [15, 97], but they can also cross the blood-brain barrier for enhanced delivery into the central nervous system, e.g., for antiretroviral drugs in HIV/AIDS [98].…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Among the wide variety of novel formulations, previous studies have shown that sonication-assisted layer-by-layer (SLBL) nanoassembly technique can be used efficiently for the nanoencapsulation of poorly soluble anticancer drugs. 14,15 Under powerful ultrasonication, the air bubble that was dissolved in water underwent the formation and implosion of the cavity, followed by the jet flow. Thus an extreme physicochemical environment was created.…”
Section: Basic Sciencementioning
confidence: 99%